RNases Disrupt the Adaptive Potential of Malignant Cells: Perspectives for Therapy - Mitkevich, Vladimir Alexandrovich; Petrushanko, Irina Yu; Makarov, Alexander Alexander (Frontiers in Pharmacology, 2019)
Exogenous RNases are selectively toxic to tumor cells. The reasons for this selectivity are not quite clear and should be searched for in the properties that distinguish malignant from normal cells. During onco-transformation, cells acquire properties allowing them to adapt to the altered microenvironment, such as resistance to hypoxia, changes in intracellular pH, disruption of ion transport, reduced adhesion and increased mobility, and production of specific exosomes. These adaptation mechanisms distinguish malignant cells from normal ones and give them a competitive advantage, ensuring survival and spread in the organism. Here, we analyze if the directed cytotoxic effect of exogenous RNases is linked to the disruption of the adaptive potential of tumor cells and how it can be used in anticancer therapy.